A Comparative Risk Analysis of Islamic and Non Islamic Bank in Indonesia from 2004 to 2014 Using Financial Ratios - Syahrani, Erina Ayunda; Fathurohman, Taufik (Journal of Business and Management, 2016)
Abstrack. The development and growth of Islamic finance in Indonesia has gone rapidly since it started in 1990. The Islamic finance has cover banking industry, made Islamic banks and Islamic Business Unit (UUS) that is under the control of established banks. As Islamic banks got stronger in the market, it concluded that Islamic Banks have to compete against conventional banks and other type of bank in Indonesia. Therefore, this study analyzed the financial performance of Islamic or Sharia banks, compared with conventional banks in Indonesia. This study will focus on risk ratio of Islamic banks and conventional banks. This study study 78 (observation) islamic banks, 232 Islamic Business Unit (UUS) and 1227Non Islamic Banks in Indonesia during 2004-2014 with risk ratios, which are Deposits to Assets (DTA), Equity Multiplier (EM), Equity to Deposts (ETD), Total Liabilities to Equity (TLE), Total Liabilities to Shareholder Capital (TLSC), and Retained Earnings to Assets (RETA). The data collected are secondary data which obtained from Otoritas Jasa Keuangan (OJK), include the income statement, balance sheet, statement of change in stockholdersâ€™ equity, and statement of cash flows. The findings shows there are differences between eight ratios that are used for the study. Findings from the calculation in previous chapter shows that Islamic Banks are statistically less risky than Non Islamic Banks, especially from 2004-2008, 2012 and 2014, based on the mean and median results. The results happen because of the change in risk components within the studied banks through years. Plus, there are also few changes in number of banks included in the calculation in 2009-2011 and 2013, that cause a difference from other studied years.Â Keywords: Islamic bank, Risk, Ratio Analysis